Mid‐life and late‐life vascular risk factor burden and neuropathology in old age - Conner, Sarah C.; Pase, Matthew P.; Carneiro, Herman; Raman, Mekala R.; McKee, Ann C.; Alvarez, Victor E.; Walker, Jamie M.; Satizabal, Claudia L.; Himali, Jayandra J.; Stein, Thor D.; Beiser, Alexa; Seshadri, Sudha (Annals of clinical and translational neurology, 2019)
Objective To determine whether vascular risk factor burden in mid‐ or late‐life associates with postmortem vascular and neurodegenerative pathologies in a community‐based sample. Methods We studied participants from the Framingham Heart Study who participated in our voluntary brain bank program. Overall vascular risk factor burden was calculated using the Framingham Stroke Risk Profile (FSRP). Mid‐life FSRP was measured at 50 to 60 years of age. Following death, brains were autopsied and semi‐quantitatively assessed by board‐certified neuropathologists for cerebrovascular outcomes (cortical infarcts, subcortical infarcts, atherosclerosis, arteriosclerosis) and Alzheimer’s disease pathology (Braak stage, cerebral amyloid angiopathy, and neuritic plaque score). We estimated adjusted odds ratios between vascular risk burden (at mid‐life and before death) and neuropathological outcomes using logistic and proportional‐odds logistic models. Results The median time interval between FSRP and death was 33.4 years for mid‐life FSRP and 4.4 years for final FSRP measurement before death. Higher mid‐life vascular risk burden was associated with increased odds of all cerebrovascular pathology, even with adjustment for vascular risk burden before death. Late‐life vascular risk burden was associated with increased odds of cortical infarcts (OR [95% CI]: 1.04 [1.00, 1.08]) and arteriosclerosis stage (OR [95% CI]: 1.03 [1.00, 1.05]). Mid‐life vascular risk burden was not associated with Alzheimer’s disease pathology, though late‐life vascular risk burden was associated with increased odds of higher Braak stage (OR [95% CI]: 1.03 [1.01, 1.05]). Interpretation Mid‐life vascular risk burden was predictive of cerebrovascular but not Alzheimer’s disease neuropathology, even after adjustment for vascular risk factors before death.